1998
DOI: 10.1111/j.1399-0039.1998.tb03026.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of HLA class II genes in Japanese patients with pemphigus vulgaris

Abstract: Pemphigus vulgaris (PV) is an autoimmune disease mediated by autoantibodies that bind to a keratinocyte adhesion molecule, desmoglein-3. The purpose of this study was to identify critical amino acid residues of PV-associated HLA class II genes. Haplotype and allele distributions, along with molecular polymorphisms, of HLA class II genes were analyzed based on the polymerase chain reaction-restriction fragment length polymorphism in 17 Japanese PV patients. Each patient had one or two alleles of DRB1*04 (*0403,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
2
17
0
4
Order By: Relevance
“…Our results confirm previous reports showing a strong association of PV with DQB1*0503 which is in linkage disequilibrium with DR14 alleles [3,4,5,8,10,12,13,14,15,16,17]. Since the DQB1*0503 PV patients had various DRB1*14 related alleles, one alternative The AA residues are shown using the letter code.…”
Section: Pemphigus Vulgarissupporting
confidence: 92%
See 3 more Smart Citations
“…Our results confirm previous reports showing a strong association of PV with DQB1*0503 which is in linkage disequilibrium with DR14 alleles [3,4,5,8,10,12,13,14,15,16,17]. Since the DQB1*0503 PV patients had various DRB1*14 related alleles, one alternative The AA residues are shown using the letter code.…”
Section: Pemphigus Vulgarissupporting
confidence: 92%
“…In PV Japanese patients, additional DRB1* PV-related alleles were observed: DRB1*0406, 1405 and 1406 [15,16,17]. We have shown that the pockets of the DRB1*1401, 05, 06 and 0406 molecules have great similarities (Table 2A) suggesting that all these PV-associated DR molecules may present the same self-peptide(s).…”
Section: Pemphigus Vulgarismentioning
confidence: 76%
See 2 more Smart Citations
“…However, population studies of patients with PV have clearly shown that there are differences among the most prevalent alleles in various ethnic groups (summarized in Table 1). Nine DRB1 alleles have been associated with PV (DRB1*0402, *0403, *0406, *0802, *0804, *1401, *1404, *1405, *1408) in 11 distinct populations [12][13][14][15][16][17][18][19][20]. Two DQB1 alleles, DQB1*0302 and DQB1*0503, are associated with PV patients across the world as well [9,12,13,15,19,21].…”
Section: Introductionmentioning
confidence: 99%